Photomemory and Pulse Monitoring Featured Solution‐Processed Near‐Infrared Graphene/Organic Phototransistor with Detectivity of 2.4 × 1013 Jones. (29th June 2021) - He, Zeyu; Han, Jiayue; Du, Xiaoyang; Cao, Luye; Wang, Jun; Zheng, Caijun; Lin, Hui; Tao, Silu
Abstract: Emerging graphene/organic phototransistors are eye‐catching technologies owing to their unique merits including easy/low‐cost fabrication, temperature independent, and achieving various functions. However, their development in the near‐infrared (NIR) region is experiencing a bottleneck of inferior sensitivity due to low exciton dissociation efficiency and inefficient charge extraction rate. Here, a novel‐design solution‐processed graphene/organic NIR phototransistor is reported, that is, creatively introducing electron extraction layer of ZnO on graphene channel and employing organic ternary bulk heterojunction as photosensitive layer, successfully breaking that bottleneck. The phototransistor exhibits a high responsivity of 6.1 × 10 6  A W −1, a superior detectivity of 2.4 × 10 13 Jones, and a remarkable minimum detection power of 1.75 nW cm −2 under 850 nm radiation. Considering its excellent NIR detection performance, a noncontact transmission‐type pulse monitoring is carried out with no external circuit support, from which human pulse signal and heart rate can be displayed in real time. The phototransistor, interestingly, can be switched into a photomemory function with a retention time of 1000 s in the atmosphere through a gate voltage of −20 V. The design takes the characteristics of graphene/organic phototransistors to a higher level, beyond the limit of sensitivity, and opens up a novel approach for developing multifunction devices. Abstract : A novel‐design near‐infrared graphene/organic phototransistor with configuration of graphene/ZnO/organic ternary bulk heterojunction is realized via solution processing. The device exhibits a superior detectivity of 2.4 × 10 13 Jones and a remarkable minimum detection power of 1.75 nW cm −2 . Additionally, the phototransistor features dual function of human signal detection and photomemory in the near‐infrared region.